(3acGgI GdHUQ hGdSeY aj eYQaI GdbQGYGJ GdSHYs - (3GdUfYGfjs
(3ChdgG (B:s
(3GdbSe GdKGdK ai ePgH MeRI hgTGe ai Gdhba Ydi GdgeR GdeaQO hGYde Cf gPG GdbSe jMJGL Edi eYQaI JMbjb ePGgH Cgd GdYQHjI s
(3BNQgG (B:s
(3dGjcda Gddg faSkG ZdG eG CJGgG , hfMf Ef TGA Gddg TGQYhf ai aQT GdMQha eSJYjf HGddg GdLRA GdKGfi ef acGgI s
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs